STRATEGI GURU DALAM MENINGKATKAN PEMAHAMAN FIKIH PESERTA DIDIK - Istanti Dalila; Sudianto (JIP: Jurnal Ilmu Pendidikan, 2026)
Understanding fiqh is an essential aspect of Islamic religious education, as it is directly related to the practice of worship and daily life of students. However, various challenges are still encountered in the learning process, such as low learning motivation, differences in students’ abilities, and the use of less varied teaching methods. Therefore, this study aims to examine teachers’ strategies in improving students’ understanding of fiqh. This research employs a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. The findings indicate that teachers’ strategies in enhancing students’ understanding of fiqh include the use of varied learning methods, such as discussions, demonstrations, and practical activities, the utilization of relevant learning media, and the provision of continuous motivation and guidance. In addition, teachers adapt their teaching strategies to the characteristics and abilities of students. The application of appropriate strategies can significantly improve students’ understanding of fiqh. This study is expected to serve as a reference for teachers in developing more effective and contextual fiqh learning strategies.